Hidden in the night - Goddard, Elizabeth (Goddard, Elizabeth. Missing in Alaska, 2024)
"Rare book collector Ivy Elliott's trip to retrieve a long-lost Jack London manuscript takes an unexpected turn when she learns the artifact isn't where it's supposed to be. Her search for answers reunites her with Alaska State Trooper Nolan Long, and they join forces to solve a decades-old mystery found hidden beneath the ice"--